1996
DOI: 10.1002/(sici)1097-4628(19960307)59:10<1619::aid-app14>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and flame-retardant properties of phosphorus-containing polymers based on poly(4-hydroxystyrene)

Abstract: SYNOPSISPhosphorus-containing polystyrene was obtained through incorporating phosphate groups onto poly(4-hydroxystyrene). This was achieved by esterification with diethylchlorophosphate. The phosphorylation was confirmed by IR, 'H-NMR, and 31P-NMR analysis. By varying the feeding ratios of the reactants, the phosphorus content in the polymers could be successfully tailored and gave values of 12.8 to 4.9% by weight. This was further corroborated by elemental analysis. Thermal characteristics and temporal stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(48 citation statements)
references
References 0 publications
3
45
0
Order By: Relevance
“…The neat EP is highly combustible, and its LOI value is only 22.0%. It is clear that the higher is the phosphorus content, the higher is the LOI value, which agrees well with previous reports 19. The LOI value of EP/TGICP composite with 10 wt% TGICP is as high as 35.0%, and it can obtain the V‐0 rating in the UL‐94 protocol.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The neat EP is highly combustible, and its LOI value is only 22.0%. It is clear that the higher is the phosphorus content, the higher is the LOI value, which agrees well with previous reports 19. The LOI value of EP/TGICP composite with 10 wt% TGICP is as high as 35.0%, and it can obtain the V‐0 rating in the UL‐94 protocol.…”
Section: Resultssupporting
confidence: 91%
“…However, the phosphorus content of these compounds is not very high, so efforts have been made to develop new flame retardant systems for epoxy resins with higher flame retardant efficiency. Some studies indicate that a significant development of flame retardant efficiency is observed when phosphorus and nitrogen are present together in the epoxy resin system 15–19. Therefore, compositions containing two or more flame retardant elements are of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Previous efforts dedicated for the synthesis of non-halogenated FRs were primarily on compounds containing phosphorus (Weil et al, 1999), silicon (Zaikov andLomakin, 1998) and boron (Armitage et al, 1996). Simple co-polymerization of epoxies (Lin et al, 2000), vinyls (Liu et al, 1996) and acrylics (Banks et al, 1994) with phosphate monomers, linear polyphosphazenes and aromatic cyclic phosphazenes (Allen, 1994) are the broad categories of phosphorous containing non-halogenated FRs. Among silicon containing compounds, polymers based on linear silanes/siloxanes (Masatoshi and Serizawa, 1998) and silsesquioxanes (Provatas and Matisons, 1997) are being extensively investigated.…”
Section: Need For Alternative Fr Materials Through 'Green' Initiativessupporting
confidence: 92%
“…The cured BPHPPO-EP produced much less fumes than the cured TBBA-EP during combustion. So the flame retardance could be enhanced remarkably by raising the content of phosphorus in the epoxy resins, and when at a similar molar proportion in the compound, the phosphorus element also exhibited much better flame retardancy than the bromine element did [14,17].…”
Section: Loi Test Of the Cured Epoxy Resinsmentioning
confidence: 99%